Structural stability and thermodynamic properties of (Y2O3)n (n = 1–15) clusters based on density functional theory. Issue 23 (11th August 2021) - Jiang, Xin; Zhang, Zhenming; Luo, Diqiang; You, Jinglin; Lai, Chaobin
Abstract: The initial configuration of Yttrium oxide clusters (Y2 O3 ) n ( n  = 1–15) was creatively constructed by combining artificial bee colony algorithm with density functional theory. The structures of large and medium‐sized yttrium oxide clusters with molecular number greater than 10 were established for the first time, and many new structures that are different from existing research have been obtained. Studies have shown that for small‐sized clusters, the atomic stacking structure is cage‐like, while for medium‐sized and large‐sized clusters, the composite trapezoidal structure and ellipsoid‐like structure are more stable. The nanoclusters tend to be stable as a whole, and the relative stability of the cluster structure is higher when n  = 2, 4, 7, 9. The heat capacity (Cp), enthalpy change (H) and entropy ( S ) of (Y2 O3 ) n ( n  = 1–15) clusters increase with the increase of temperature (T), and the vibration free energy (Gv) decreases with the increase of T. Abstract : The initial configuration of Yttrium oxide clusters (Y2 O3 ) n ( n  = 1–15) was creatively constructed by combining artificial bee colony algorithm with density functional theory. The average binding energy, second‐order difference energy, H–L energy gap, density of states and thermodynamic properties of the clusters were analyzed in detail, which laid a foundation for revealing the formation mechanism of transitional yttrium oxide crystals and the doping of cluster elements in the two‐step nucleation process.